ANALISIS SOSIOLOGI SASTRA PADA TOKOH JOSE KAROSTA DALAM NASKAH MASTODEN DAN BURUNG KONDOR KARYA W.S RENDRA - Putri Schatzi Abdillah; Aura Kirana Maharani; Irena Mulyana Syabilla; Nurul Camilah Rahdianti; Sabila Fitriani; Muhammad Prasetyo Nugroho (Jurnal Bastra (Bahasa dan Sastra), 2025)
This study examines the character of Jose Karosta in the drama script "Mastodon dan Burung Kondor" by W.S. Rendra using a sociology of literature approach. The purpose of this study is to analyze the characteristics of the character of Jose Karosta, identify the social criticism represented through the character, and examine the relationship between the character of Jose Karosta and the socio-political conditions of Indonesia at the time the script was written. This study uses a qualitative descriptive method with content analysis techniques. Data were collected through literature studies with reading and note-taking techniques. The results of the study show that the character of Jose Karosta represents a critique of social inequality, economic imperialism, and structural injustice that occurs in society. Through the character of Jose Karosta, Rendra criticizes the dominance of foreign powers, the exploitation of natural resources, and describes the struggle of the indigenous people in facing the power of neocolonialism. The sociology of literature analysis of the character of Jose Karosta shows that W.S. Rendra uses literature as a medium of resistance against the hegemony of power and to voice the aspirations of the oppressed people. This study concludes that the representation of the character Jose Karosta in "Mastodon dan Burung Kondor" is a reflection of the socio-political conditions of Indonesia during the New Order era and a manifestation of Rendra's critical views on social injustice.